Retractable congestive heart failure due to sinus valsalva rupture with coexisting gerbode defect: a rare case report - Bestya Presidiana; Anudya Kartika Ratri; Ririn Ramli; Andrianto; Arief Rakhman Hakim (Journal of the Pakistan Medical Association, 2024)
Sinus of Valsalva aneurysm (SoVA) is a rare disease with less than 1% prevalence in the population. Most cases are asymptomatic, however, significant clinical manifestations are possible due to fistula formation and sudden rupture resulting in cardiac shunt. Eventually it may develop into progressive heart failure with high morbidity. We report the case of a 33 year old female patient who presented with shortness of breath, ascites, and recurring hospitalisation. The cardiac examination revealed sinus tachycardia along with loud and continuous murmurs on the left parasternal border. Several standard diagnostic procedures could not be performed due to malignant arrhythmia in supine position. Echocardiography examination revealed SoV rupture with a gerbode defect, which was the underlying cause of severe retractable heart failure. Keywords: Sinus of Valsalva Aneurysm, Supine Position, Aortic Aneurysm, Heart Septal, Ventricular, Heart Murmurs, Fistula, Arrhythmias, Cardiac, Dyspnoea, Tachycardia